2014
DOI: 10.3126/jnps.v34i2.10566
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Under-Five Children in Western Nepal

Abstract: Introduction: Undernutrition is a major health problem in developing countries which may have adverse effects on growth and development of an individual. The objectives of this study were to assess the prevalence and grades of malnutrition in children below 60 months of age, attending outpatient department at Gandaki Medical College teaching hospital. Materials and Methods: A prospective study was conducted among 556 children below 60 months of age from August to December 2013. Weight and length/height were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
3
1
Order By: Relevance
“…These figures were little higher than reported in the Annual report of Nepal 2016. [1] Similarly, these figures are higher than the rate shown in other studies done in Pokhara, [6] Dolakha, [7] Humla, [8] and Ilam [9] but lower than the studies done in Kathmandu and Eastern Terai. [ …”
Section: Discussioncontrasting
confidence: 53%
“…These figures were little higher than reported in the Annual report of Nepal 2016. [1] Similarly, these figures are higher than the rate shown in other studies done in Pokhara, [6] Dolakha, [7] Humla, [8] and Ilam [9] but lower than the studies done in Kathmandu and Eastern Terai. [ …”
Section: Discussioncontrasting
confidence: 53%
“…The data compiled by Chaparro et al in 2014 showed that the greatest increases in stunting in Nepal were taking place in infants aged between 9 and 18 mo due to inadequate breastfeeding and complementary feeding and the rise in illness and infection at this age ( 51 ). An additional 5 studies supported this finding of higher rates or worsening in the severity of stunting among older infants in Nepal ( 35 , 43 , 62 , 63 , 64 ). Access to health services, and particularly maternal and newborn health care, has been linked to a reduction in stunting in Nepal by 7 studies ( 5 , 6 , 29 , 36 , 37 , 55 , 56 ).…”
Section: Introductionmentioning
confidence: 83%
“…In particular, a 2016 study by Cunningham et al found, through regression analysis of Nepal's DHS data from 1996 to 2011, that there was a relative contribution of 0.18 SDs to HAZ among children who received all of their vaccinations ( 5 ). Conversely, 2 studies included in this literature review found an association between infection and illness in Nepalese children and poor growth outcomes ( 64 , 65 ). Maternal nutrition was also linked to child growth outcomes in 7 studies.…”
Section: Introductionmentioning
confidence: 85%
“…2 The prevalence of wasting and underweight was found somehow similar with the nutritional status of under five children in Western Nepal where 15.1% were wasted and 20.2% were underweight respectively but the stunting was somehow lower in Duruwa VDC than in western Nepal. 6 The inappropriate time of initiation of complementary feeding, outbreaks of diarrhea and other diseases may be the reason behind this. This may be due to low hygiene and sanitation in the community which may cause disease outbreak and parasitic infection in children causing wasting in children.…”
Section: Discussionmentioning
confidence: 99%